Warr;or21: A 21-Day Program to Enhance First Responder Resilience and Mental Health - Thompson, Jeff; Drew, Jacqueline M. (Frontiers in Psychology, 2020)
First responders face multiple stressors on a daily basis. They have experienced higher rates of anxiety disorders, depression, burnout, post-traumatic stress disorder (PTSD), suicide (Asmundson & Stapleton, 2008), alcohol and substance abuse (Ballenger et al., 2010), and deficient sleep hygiene (Pearsall, 2012) compared to the general population. Existing resilience research can be utilized and adapted to help first responders cope in a positive manner as a form of prevention and also as part of their recovery. New resiliency programs continue to emerge and this paper details one – warr;or21. The warr;or21 program is explained and based on an evaluation of the program’s preliminary data, the results are promising with how the program can assist first responders (and the general public) increase their resiliency and mental health.